2015
DOI: 10.1161/hypertensionaha.115.05449
|View full text |Cite
|
Sign up to set email alerts
|

Refractory Hypertension

Abstract: Refractory hypertension is an extreme phenotype of treatment failure defined as uncontrolled blood pressure (BP) in spite of ≥5 classes of antihypertensive agents, including chlorthalidone and a mineralocorticoid receptor antagonist. A prospective evaluation of possible mechanisms of refractory hypertension has not been done. The goal of this study was to test for evidence of heightened sympathetic tone as indicated by 24-hr urinary (U-) normetanephrine levels, clinic and ambulatory heart rate (HR), HR variabi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
65
0
21

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 105 publications
(88 citation statements)
references
References 44 publications
(52 reference statements)
2
65
0
21
Order By: Relevance
“…In the present study, 7.9% of RH had RfH. Dudenbostel et al9, 17 reported that the prevalence of RfH in a referral hypertension unit was ≈5%, and Calhoun et al8 estimated a prevalence of RfH of 3.6% of subjects with controlled or uncontrolled RH. The slightly higher prevalence observed in our study could be explained by 2 reasons: first, because low BP control is one of the main indications for ABPM, it is possible that the Spanish Registry was selecting more subjects with difficult‐to‐treat hypertension than other population‐based studies.…”
Section: Discussionsupporting
confidence: 49%
“…In the present study, 7.9% of RH had RfH. Dudenbostel et al9, 17 reported that the prevalence of RfH in a referral hypertension unit was ≈5%, and Calhoun et al8 estimated a prevalence of RfH of 3.6% of subjects with controlled or uncontrolled RH. The slightly higher prevalence observed in our study could be explained by 2 reasons: first, because low BP control is one of the main indications for ABPM, it is possible that the Spanish Registry was selecting more subjects with difficult‐to‐treat hypertension than other population‐based studies.…”
Section: Discussionsupporting
confidence: 49%
“…Furthermore, sympathetic activation is higher in patients with TRH than in individuals with elevated BP who respond to antihypertensive drug administration. In a recent study, Dudenbostel and colleagues found increased 24-hour urinary normetanephrine levels in patients with uncontrolled TRH, suggesting that heightened sympathetic tone might be partly responsible for antihypertensive treatment failure [10]. Importantly, these findings support expanded efforts to design denervation device-based interventions to treat TRH.…”
Section: Fluid Expansion Salt Sensitivity and Sympathetic Activationmentioning
confidence: 87%
“…In a retrospective analysis of 304 patients with TRH, Acelajado et al identified that 29 (9.5%) remained refractory to treatment, despite maximal antihypertensive therapy [21]. Likewise, a prospective analysis of 559 patients with TRH revealed that 15 (2.6%) of patients sustained uncontrolled BP, in spite of treatment with more than 5 classes of antihypertensive agents [10]. …”
Section: Potential New Directions For Therapy Of Trhmentioning
confidence: 99%
“…In addition, there is evidence for excessive aldosterone secretion, including high plasma aldosterone levels, albeit not as high as in patients with primary aldosteronism, and BP responsiveness to mineralocorticoid receptor antagonists (1,3,4). A small subset (2.7%) of RH, requiring ≥ 5 classes of antihypertensive agents for BP control, has recently been termed “refractory hypertension” (7). These patients may have different pathophysiologic mechanisms for treatment failure, especially excessive sympathetic output as evidenced by greater urinary 24h normetanephrine levels, greater arterial stiffness, higher heart rate, lower heart rate variability, and higher systemic vascular resistance than patients with controlled RH (7).…”
mentioning
confidence: 99%
“…A small subset (2.7%) of RH, requiring ≥ 5 classes of antihypertensive agents for BP control, has recently been termed “refractory hypertension” (7). These patients may have different pathophysiologic mechanisms for treatment failure, especially excessive sympathetic output as evidenced by greater urinary 24h normetanephrine levels, greater arterial stiffness, higher heart rate, lower heart rate variability, and higher systemic vascular resistance than patients with controlled RH (7). …”
mentioning
confidence: 99%